Differential uptake of recent Papanicolaou testing by HPV vaccination status among young women in the United States, 2008–2013. Issue 4 (August 2015) - Sauer, Ann Goding; Jemal, Ahmedin; Simard, Edgar P.; Fedewa, Stacey A.
Highlights Women who had not initiated HPV vaccination less likely to have recent Pap test. Overall observation was consistent across most sociodemographic factors. Asians/others without HPV vaccine less likely than Whites to have recent Pap test.